Affirmative action in medicine : improving health care for everyone - Curtis, James L., 1922- (University of Michigan Press, 2003)
"Advancing arguments from his earlier book, Blacks, Medical Schools, and Society, Curtis evaluates the outcomes of affirmative action efforts over the past thirty years. He describes formidable barriers to minority access to medical-education opportunities and the resulting problems faced by minority patients in receiving medical treatment. His progress report includes a review of two thousand minority students admitted to U.S. medical schools in 1969, following them through graduation and their careers and comparing them with two thousand of their nonminority peers. These samples provide an important look at medical schools that, while heralding dramatic progress in physician education and training opportunity, indicates much room for further improvement."--Jacket